Deep Brain Stimulation in Gilles de la Tourette Syndrome: What Does the Future Hold? A Cohort of 48 Patients. Issue 1 (4th September 2015) - Servello, Domenico; Zekaj, Edvin; Saleh, Christian; Lange, Nicholas; Porta, Mauro
Abstract: BACKGROUND: Gilles de la Tourette syndrome (GTS) is a severe neuropsychiatric disorder with childhood onset, characterized by disabling motor and vocal tics lasting for more than 1 year and associated with a wide range of psychiatric comorbidities. Pharmacological treatment is indicated for moderate to severe GTS patients. However, when GTS is refractory to conventional medical and behavioral treatments, deep brain stimulation (DBS) can be considered as a last resort therapeutic avenue. OBJECTIVE: To evaluate the efficacy of DBS and its comorbidities in the largest pool of GTS patients to date. METHODS: Our cohort study was based on 48 patients' refractory to conventional treatment who underwent DBS for GTS at Galeazzi Institute, Milan, Italy. An exhaustive preoperative and a follow-up battery of tests was performed including the Yale Global Tic Severity Rating Scale, the Yale-Brown Obsessive Compulsive Scale, the Beck Depression Inventory, the State Trait Anxiety Inventory, and the Subjective Social Impairment on a 10-point Visual Analogue Scale tests. RESULTS: Eleven patients in whom the device was removed for inflammatory complications or for poor compliance were excluded from final analysis. Twenty-seven of the remaining 37 patients had a Yale Global Tic Severity Rating Scale score at the last follow-up that was less than 35. Of the 37 patients, in 29 cases (78%) a reduction of more than 50% of the Yale Global Tic Severity Rating Scale score was observed. CONCLUSION: The clinical efficacy of DBS in GTS is promising. Although DBS is associated with risks, as is any surgical intervention, DBS should be considered as a last resort therapeutic option in carefully selected GTS patients.